To solve this problem, we just have to substitute the values into the exponential equations and solve.
Exponential Equation
In the given exponential equation, we simply need to plug in the values of x from 0 to 5
[tex]y = 4(3)^x[/tex]
when x = 0
[tex]y = 4(3)^x\\y = 4(3)^0\\y = 4[/tex]
when x = 1
[tex]y = 4(3)^x\\y = 4(3)^1\\y = 12\\[/tex]
when x = 2
[tex]y = 4(3)^2\\y = 36[/tex]
when x = 3
[tex]y = 4(3)^3\\y = 108[/tex]
when x = 4
[tex]y = 4(3)^4\\y = 324[/tex]
when x = 5
[tex]y = 4(3)^5\\y = 972[/tex]
From the calculations above, the value of y when x is from 0 to 5 are
- x(0) = 4
- x(1) = 12
- x(2) = 36
- x(3) = 108
- x(4) = 324
- x(5) = 972
Learn more on exponential equations here;
https://brainly.com/question/12347013
#SPJ1